Cemento-Osseous dysplasia: Diagnosis and treatment of 21 cases - LIU Xianguang; YAN Shuyun; WANG Xuxia (Kouqiang hemian waike zazhi)
[Objective:] To investigate the clinical characteristics of cemento-osseous dysplasia(COD). [Methods:] The clinical diagnostic and treatment data of 21 patients with COD were collected. The clinical manifestations (age, gender, location, symptoms and signs), imaging characteristics, intraoperative conditions and prognosis were recorded and analyzed retrospectively. [Results:] Among the 21 cases, the incidence rate of female were higher than that of male, and 40-49 years old was the predilection age, accounting for 52.4%. 52.4% of the patients had no clinical symptoms. The lesions mostly located in mandible. Cortical bone expansion and missing teeth were common signs, accounting for 57.1%. 38.5% of the lesions caused mandibular canal displacement without lower lip numbness, and 30.8% of the lesions caused root resorption of the adjacent teeth. In radiological imaging, 69.2% of the lesions were mainly transparent and 30.8% were mainly resistant. Surgical treatment was effective for the disease, and new bone formation is found in the lesion area after operation. [Conclusion:] COD is a rare structural disorder of jaw. The incidence rate in female patients is significantly higher than that of male. It has a predilection for the mandible. Most patients have no clinical symptoms, and some infections can occur. Surgical resection is beneficial for bone regeneration.